Monte Carlo simulation of a NaI detector in the aquatic environment - Bagatelas, C.; Tsabaris, C.; Kokkoris, M.; Papadopoulos, C. T.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
NaI(Tl) crystals are used in many marine applications for continuous measurements with buoy operation and autonomous in situ measurements in seawater. Monte Carlo simulations were performed using the GEANT4 code for the investigation of the γ-ray absorption in water in different spherical geometries and for the efficiency of a NaI(Tl) detector of different radionuclides in the aquatic environment. In order to test the reliability of these simulations, experimental values of the NaI(Tl) detector efficiency were deduced using a special tank filled with water and reference single gamma ray sources (99mTc, 137Cs and 40K). The cascade reference source 111In was also diluted in tank for comparison with the reproduction spectra of its cascade lines as provided with the GEANT4 code. The results are in good agreement with the simulated ones within uncertainties.